Stallion in the storm - Daniels, Lucy; Baum, Ann (Hodder Children's London, 1999)
Mandy and James can hardly wait to accompany her dad to Folan's Racing Stables. But they find that Folan's is in trouble. Some of the jockeys believe it's because the stables are haunted by Tibor, one of their stallions, who died in a race. Can Mandy and James discover the truth - and help Tibor make his peace?